Basic and other measurements of radiation at station Gobabeb (2022-01) - Roland Vogt (PANGAEA, 2022)
In Gobabeb, Namibia SWD, LWD and DIR are each measured redundant with two instruments of the same make (not in this data base). The differences between the pairs are used in the quality control. This is done manually by inspecting plots of half-day diurnal courses of the pairs and their differences. Values are removed mostly in the morning due to daily cleaning. Other reasons for larger differences are birds, insects, or people at the station. There are regular fog events varying in frequency over the year. Usually, the fog appears in the second half of the night and disappears a few hours after sunrise. The case temperatures of pyrgeometers practically never drop below dewpoint but there can be water deposition of the dome.
In: Vogt, R (2024): Basic and other measurements of radiation at station Gobabeb (2012-05 et seq) [dataset publication series]. Atmospheric Sciences, Department of Environmental Sciences, University of Basel, PANGAEA, https://doi.org/10.1594/PANGAEA.968639